Newton’s Method and Secant Method for Set-Valued Mappings - Baier, Robert; Molo, Mirko Hessel-von (Large-Scale Scientific Computing)

Modelling and Analysis of the Nonlinear Dynamics of the Transrapid and Its Guideway - Dellnitz, Michael; Dignath, Florian; Flaßkamp, Kathrin; Molo, Mirko Hessel-von; Krüger, Martin; Timmermann, Robert; Zheng, Qinghua (Mathematics in Industry)

Energy efficient control for mechanical systems based on inherent dynamical structures - Flaskamp, K.; Ober-Blobaum, S. (2012 American Control Conference (ACC))

Switching time optimization in discretized hybrid dynamical systems - Flasskamp, Kathrin; Murphey, Todd; Ober-Blobaum, Sina (2012 IEEE 51st IEEE Conference on Decision and Control (CDC))

Solving Optimal Control Problems by Exploiting Inherent Dynamical Systems Structures - Flaßkamp, Kathrin; Ober-Blöbaum, Sina; Kobilarov, Marin (Journal of Nonlinear Science)

Optimal Control on Stable Manifolds for a Double Pendulum - Flaßkamp, Kathrin; Timmermann, Julia; Ober-Blöbaum, Sina; Dellnitz, Michael; Trächtler, Ansgar (PAMM)

Three-dimensional characterization and tracking of an Agulhas Ring - Froyland, Gary; Horenkamp, Christian; Rossi, Vincent; Santitissadeekorn, Naratip; Gupta, Alex Sen (Ocean Modelling)

Discontinuity Induced Bifurcations in Timed Continuous Petri Nets - Meyer, A. (IFAC Proceedings Volumes)

Symmetry Reductions in Timed Continuous Petri Nets Under Infinite Server Semantics - Meyer, A.; Silva, M. (IFAC Proceedings Volumes)

Handling high-dimensional problems with multi-objective continuation methods via successive approximation of the tangent space - Ringkamp, Maik; Ober-Blöbaum, Sina; Dellnitz, Michael; Schütze, Oliver (Engineering Optimization)

Multilevel Subdivision Techniques for Scalar Optimization Problems - Dellnitz, Michael; Schütze, Oliver (Global Analysis of Nonlinear Dynamics)

Intersecting invariant manifolds in spatial restricted three-body problems: Design and optimization of Earth-to-halo transfers in the Sun–Earth–Moon scenario - Zanzottera, A.; Mingotti, G.; Castelli, R.; Dellnitz, M. (Communications in Nonlinear Science and Numerical Simulation)

Faculty Submitted Student Work at Siggraph 2012 - Domik, Gitta (Curated exhibit at Siggraph)

Modelling and Analysis of the Nonlinear Dynamics of the Transrapid and Its Guideway - Dellnitz, Michael; Dignath, Florian; Flaßkamp, Kathrin; Molo, Mirko Hessel-von; Krüger, Martin; Timmermann, Robert; Zheng, Qinghua (Mathematics in Industry)

Reducing classification accuracy degradation of pattern recognition based myoelectric control caused by electrode shift using a high density electrode array - Boschmann, Alexander; Platzner, Marco (Proc. IEEE Int. Conf. Eng. Med. Biolog. (EMBC))

Design and Implementation of a Nanophotonics Simulation Personality for the Convey HC-1 Hybrid Core Computer - Dridger, Denis

Design and Programming of Reconfigurable Mesh based Many-Cores - Giefers, Heiner
The paradigm shift towards many-core parallelism is accompanied by two fundamental questions: how should the many processors on a single die communicate to each other and what are suitable programming models for these novel architectures? In this thesis, the author tackles both questions by reviewing the reconfigurable mesh model of massively parallel computation for many-cores. The book presents the design, implementation and evaluation of a many-core architecture that is based on the execution principles and communication infrastructure of the reconfigurable mesh. This work fundamentally rests on FPGA implementations and shows that reconfigurable mesh processors with hundreds of autonomous cores are feasible. Several case studies demonstrate the effectiveness of programming and illustrate why the reconfigurable mesh is a promising model for many-cores.

Adaptive Playouts in der Monte-Carlo Spielbaumsuche am Anwendungsfall Go - Graf, Tobias

Generating Adjustable Temperature Gradients on modern FPGAs - Hangmann, Hendrik

Compensating Resource Fluctuations by Means of Evolvable Hardware: The Run-Time Reconfigurable Functional Unit Row Classifier Architecture - Kaufmann, Paul; Glette, Kyrre; Platzner, Marco; Torresen, Jim (International Journal of Adaptive, Resilient and Autonomic Systems (IJARAS))

Wieder natürlich gehen und greifen - Platzner, Marco; Boschmann, Alexander; Kaufmann, Paul

Stereo Matching on a HC-1 Hybrid Core Computer - Schmitz, Henning

Entwicklung eines Picoblaze Compilers mit dem Gentle Compiler Construction System - Topmöller, Christoph

Analysis of Pattern Based Model Design and Learning in Computer-Go - Wistuba, Martin

Quality Analysis and Optimization of the MAP-based Noise Power Spectral Density Tracker - Chinaev, Aleksej; Haeb-Umbach, Reinhold (Speech Communication; 10. ITG Symposium; Proceedings.)

Improved Noise Power Spectral Density Tracking by a MAP-based Postprocessor - Chinaev, Aleksej; Krueger, Alexander; Tran Vu, Dang Hai; Haeb-Umbach, Reinhold (37th International Conference on Acoustics, Speech and Signal Processing (ICASSP 2012))
In this paper we present a novel noise power spectral density tracking algorithm and its use in single-channel speech enhancement. It has the unique feature that it is able to track the noise statistics even if speech is dominant in a given time-frequency bin. As a consequence it can follow non-stationary noise superposed by speech, even in the critical case of rising noise power. The algorithm requires an initial estimate of the power spectrum of speech and is thus meant to be used as a postprocessor to a first speech enhancement stage. An experimental comparison with a state-of-the-art noise tracking algorithm demonstrates lower estimation errors under low SNR conditions and smaller fluctuations of the estimated values, resulting in improved speech quality as measured by PESQ scores.
Keywords: MAP parameter estimation; noise power estimation; speech enhancement

Reverberant Speech Recognition - Krueger, Alexander; Haeb-Umbach, Reinhold (Techniques for Noise Robustness in Automatic Speech Recognition)

Bayesian Feature Enhancement for ASR of Noisy Reverberant Real-World Data - Krueger, Alexander; Walter, Oliver; Leutnant, Volker; Haeb-Umbach, Reinhold (Proc. Interspeech)
In this contribution we investigate the effectiveness of Bayesian feature enhancement (BFE) on a medium-sized recognition task containing real-world recordings of noisy reverberant speech. BFE employs a very coarse model of the acoustic impulse response (AIR) from the source to the microphone, which has been shown to be effective if the speech to be recognized has been generated by artificially convolving nonreverberant speech with a constant AIR. Here we demonstrate that the model is also appropriate to be used in feature enhancement of true recordings of noisy reverberant speech. On the Multi-Channel Wall Street Journal Audio Visual corpus (MC-WSJ-AV) the word error rate is cut in half to 41.9 percent compared to the ETSI Standard Front-End using as input the signal of a single distant microphone with a single recognition pass.

Investigations Into a Statistical Observation Model for Logarithmic Mel Power Spectral Density Features of Noisy Reverberant Speech - Leutnant, Volker; Krueger, Alexander; Haeb-Umbach, Reinhold (Speech Communication; 10. ITG Symposium; Proceedings of)
In this contribution, a new observation model for the joint compensation of reverberation and noise in the logarithmic mel power spectral density domain will be considered. The proposed observation model relates the noisy reverberant feature to the underlying sequence of clean speech features and the feature of the noise. Nevertheless, due to the complex interaction of these variables in the target domain, the observationmodel cannot be applied to Bayesian feature enhancement directly, calling for approximations that eventually render the observation model useful. The performance of the approximated observation model will highly depend on the capability of modeling the difference between the model and the noisy reverberant observation. A detailed analysis of this observation error will be provided in this work. Among others, it will point out the need to account for the instantaneous ratio of the reverberant speech power and the noise power. Index Terms: Bayesian feature enhancement, observation model for noisy reverberant speech

A Statistical Observation Model For Noisy Reverberant Speech Features and its Application to Robust ASR - Leutnant, Volker; Krueger, Alexander; Haeb-Umbach, Reinhold (Signal Processing, Communications and Computing (ICSPCC), 2012 IEEE International Conference on)
In this work, an observation model for the joint compensation of noise and reverberation in the logarithmic mel power spectral density domain is considered. It relates the features of the noisy reverberant speech to those of the non-reverberant speech and the noise. In contrast to enhancement of features only corrupted by reverberation (reverberant features), enhancement of noisy reverberant features requires a more sophisticated model for the error introduced by the proposed observation model. In a first consideration, it will be shown that this error is highly dependent on the instantaneous ratio of the power of reverberant speech to the power of the noise and, moreover, sensitive to the phase between reverberant speech and noise in the short-time discrete Fourier domain. Afterwards, a statistically motivated approach will be presented allowing for the model of the observation error to be inferred from the error model previously used for the reverberation only case. Finally, the developed observation error model will be utilized in a Bayesian feature enhancement scheme, leading to improvements in word accuracy on the AURORA5 database.
Keywords: Robust Automatic Speech Recognition; Bayesian feature enhancement; observation model for reverberant and noisy speech

Derivation of the Power Compensation Constant in the Observation Model for Reverberant Speech in the Logarithmic Mel Power Spectral Domain - Leutnant, Volker; Krueger, Alexander; Haeb-Umbach, Reinhold

Exploiting Temporal Correlations in Joint Multichannel Speech Separation and Noise Suppression using Hidden Markov Models - Tran Vu, Dang Hai; Haeb-Umbach, Reinhold (International Workshop on Acoustic Signal Enhancement (IWAENC2012))

Cooperative Awareness at Low Vehicle Densities: How Parked Cars Can Help See through Buildings - Eckhoff, D.; Sommer, Christoph; German, R.; Dressler, F. (2011 IEEE Global Telecommunications Conference - GLOBECOM 2011)

On the Necessity of Accurate IEEE 802.11P Models for IVC Protocol Simulation - Eckhoff, David; Sommer, Christoph; Dressler, Falko (2012 IEEE 75th Vehicular Technology Conference (VTC Spring))

Comparing apples and oranges? - Joerer, Stefan; Dressler, Falko; Sommer, Christoph (Proceedings of the ninth ACM international workshop on Vehicular inter-networking, systems, and applications - VANET '12)

Toward reproducibility and comparability of IVC simulation studies: a literature survey - Joerer, Stefan; Sommer, Christoph; Dressler, Falko (IEEE Communications Magazine)

Content downloading in vehicular networks: Bringing parked cars into the picture - Malandrino, F.; Casetti, C.; Chiasserini, C. F.; Sommer, Christoph; Dressler, F. (2012 IEEE 23rd International Symposium on Personal, Indoor and Mobile Radio Communications - (PIMRC))

Built-in Self-Diagnosis Targeting Arbitrary Defects with Partial Pseudo-Exhaustive Test - Cook, Alejandro; Hellebrand, Sybille; E. Imhof, Michael; Mumtaz, Abdullah; Wunderlich, Hans-Joachim (13th IEEE Latin American Test Workshop (LATW'12))

Built-in Self-Diagnosis Exploiting Strong Diagnostic Windows in Mixed-Mode Test - Cook, Alejandro; Hellebrand, Sybille; Wunderlich, Hans-Joachim (17th IEEE European Test Symposium (ETS'12))

GPU-based cloud computing for comparing the structure of protein binding sites - Leinweber, M.; Baumgärtner, L.; Mernberger, M.; Fober, T.; Hüllermeier, Eyke; Klebe, G.; Freisleben, B. (in Proceedings IEEE Conference on Digital Ecosystem Technologies-Complex Environment Engineering Campione d`Italia, Italy)

Efficient learning of classifiers based on the 2-additive Choquet integral - Hüllermeier, Eyke; Fallah Tehrani, A. (Computational Intelligence in Intelligent Data Analysis)

Koli Calling 2009 and 2010 - Schulte, Carsten; Suhonen, Jarkko (Computer Science Education)

Computer science at school/CS teacher education: Koli working-group report on CS at school - Schulte, Carsten; Hornung, Malte; Sentance, Sue; Dagiene, Valentina; Jevsikova, Tatjana; Thota, Neena; Eckerdal, Anna; Peters, Anne-Kathrin (Koli Calling)

Uncovering structure behind function: the experiment as teaching method in computer science education - Schulte, Carsten (WiPSCE)

Learning conditional lexicographic preference trees - Bräuning, M.; Hüllermeier, Eyke (In Workshops on Preference Learning at ECAI, European Conference on Artiticial intelligence, Montpellier, France)

A Syllable-based Prosody Modeling for L1 and L2 English Speeches - Chen, Wei-Fan; Kuo, Chin-Kuan; Wang, Yih-Ru; Chen, Sin-Horng (Proceedings of the 8th International Symposium on Chinese Spoken Language Processing)

Efficient String-Based XML Stream Prefiltering - Böttcher, Stefan; Hartel, Rita; Weber, Steffen (Proceedings of the Twenty-Third Australasian Database Conference)

Fast Insertion and Deletion in Compressed Texts - Böttcher, Stefan; Bültmann, Alexander; Hartel, Rita; Schlüßler, Jonathan (2012 Data Compression Conference)

On the VC dimension of the Choquet integral - Hüllermeier, Eyke; Fallah Tehrani, A. (In Proceedings IPMU-2012 14th International Conference on Information Processing and Management of Uncertainty in Knowledge-Based Systems, Part 1, Catania, Italy)

Learning monotone nonlinear models using the Choquet integral - Fallah Tehrani, A.; Cheng, W.; Dembczynski, K.; Hüllermeier, Eyke (Machine Learning)

Grouping, overlap and generalized bientropic functions for fuzzy modeling of pairwise comparisons - Bustince, H.; Pagola, M.; Mesiar, R.; Hüllermeier, Eyke; Herrera, F. (IEEE Transactions on Fuzzy Systems)

Preference-based reinforcement learning: A formal framework and a policy iteration algorithm - Fürnkranz, J.; Hüllermeier, Eyke; Cheng, W.; Park, S.H. (Machine Learning)

On label dependence and loss minimization in multi-label classification - Dembczynski, K.; Waegeman, W.; Cheng, W.; Hüllermeier, Eyke (Machine Learning)

IBL Streams: A system for instance-based classification and regression on data streams - Shaker, Ammar; Hüllermeier, Eyke (Evolving Systems)

A formal and empirical analysis of the fuzzy gamma rank correlation coefficient - Dolorez Ruiz, M.; Hüllermeier, Eyke (Information Sciences)

Preference learning using the Choquet integral: The case of multipartite ranking - Fallah Tehrani, A.; Cheng, W.; Hüllermeier, Eyke (IEEE Transactions on Fuzzy Systems)

Fingerprint kernels for protein structure comparison - Fober, T.; Mernberger, M.; Klebe, G.; Hüllermeier, Eyke (Molecular Informatics)

Comparing fuzzy partitions: A generalization of the Rand index and related measures - Hüllermeier, Eyke; Rifqi, M.; Henzgen, Sascha; Senge, Robin (IEEE Transactions on Fuzzy Systems)

Fuzzy Pattern Trees: Ein alternativer Ansatz zur Fuzzy-Modellierung - Senge, Robin; Fober, T.; Nasiri, N.; Hüllermeier, Eyke (At-Atomatisierungstechnik)

Asynchronous Occlusion Culling on Heterogeneous PC Clusters for Distributed 3D Scenes - Suess, Tim; Koch, Clemens; Jähn, Claudius; Fischer, Matthias; Meyer auf der Heide, Friedhelm (Advances in Visual Computing)
We present a parallel rendering system for heterogeneous PC clusters to visualize massive models. One single, powerful visualization node is supported by a group of backend nodes with weak graphics performance. While the visualization node renders the visible objects, the backend nodes asynchronously perform visibility tests and supply the front end with visible scene objects. The visualization node stores only currently visible objects in its memory, while the scene is distributed among the backend nodes’ memory without redundancy. To efficiently compute the occlusion tests in spite of that each backend node stores only a fraction of the original geometry, we complete the scene by adding highly simplified versions of the objects stored on other nodes. We test our system with 15 backend nodes. It is able to render a ≈ 350,M polygons (≈ 8.5,GiB) large aircraft model with 20, to 30,fps and thus allows a walk-through in real-time.

Geführte akustische Wellen zur Flüssigkeitscharakterisierung - Rautenberg, Jens; Bause, Fabian; Henning, Bernd (tm - Technisches Messen)

Numerische Nullstellensuche in Determinantenfunktionen mittels Intervallarithmetik und algorithmischem Differenzieren - Bause, Fabian; Walther, Andrea; Henning, Bernd

Ultrasonic sensors for process applications - Henning, Bernd; Rautenberg, Jens
Typical examples for the sensory use of ultrasound in industry are the measurement of flow, level, density, viscosity or concentration. Most commercial devices only provide one of these quantities but a microprocessor based evaluation of the measured information in connection with extended models of the measurement setup may also extend the functionality of those sensors. In this contribution some trends for further developments of ultrasound flowmeters and ultrasonic chemical sensors will be outlined. Focusing on flow measurement, some functional enhancements like flow profile correction and the simultaneous identification of the flowing medium are discussed in more detail.

Trends im Design von Ultraschallsensoren - Henning, Bernd

Korrelation hochfrequenter und quasistatischer Materialkenngrössen zur Charakterisierung verschiedener Alterungsstadien von Polyamid 6 - Bause, Fabian; Budde, Christopher; Rautenberg, Jens; Henning, Bernd; Moritzer, Elmar
Polyamid 6 (PA 6), stammend aus der Gruppe der Polykondensate, ist ein thermoplastischer Kunststoff und zeichnet sich u.a. durch eine hohe Festigkeit und Steifigkeit bei geringen Rohstoff- und Herstellungskosten aus. Das Einsatzgebiet von Polyamiden ist sehr vielseitig. Neben dem massiven Einsatz in der Textilindustrie sei beispielsweise auch der Einsatz in Seilen und Trassen, Zahnrädern und Lagern genannt. Weiterhin findet PA 6 kompositäre Verwendung als Matrixmaterial in thermoplastischen Faserverbundmaterialien (u. a. endlosfaserverstärkte Organobleche) und ist dabei vor allem für die Automobilindustrie von immens steigender Bedeutung. Neben der bei PA ausgeprägten reversiblen Polykondensation, d.h. der Reaktion des Kunststoffes mit Wasser aus der Umgebungsluft, treten irreversible Prozesse (Thermooxidation, Photooxidation, Nachkondensation, $…$) auf, welche seine chemischen und mechanischen Eigenschaften beeinflussen. In diesem Beitrag sollen die Auswirkungen hydrothermischer Alterung durch Temperatur und Feuchtigkeit, auf die akustischen bzw. mechanischen Eigenschaften zum einen im hochfrequenten (Ultraschall) und zum anderen im quasistatischen Bereich charakterisiert werden. Dazu werden PA 6 Probekörper mittels Klimawechseltests künstlich gealtert und in zwei verschiedenen Versuchsaufbauten beurteilt. Zum einen werden hohlzylindrische Proben zur Charakterisierung im Ultraschallbereich (Schallgeschwindigkeit, Schallkennimpedanz, Schallabsorption) und zum anderen Schulterstäbe zur Charakterisierung der mechanischen Materialeigenschaften im quasistatischen Bereich verwendet. Die akustischen Materialkenngrößen der Ultraschallcharakterisierung und die mechanischen Materialkenngrößen aus dem quasistatischen Bereich, werden abschließend miteinander korreliert und Zusammenhänge dargestellt.

Sensitivity study of signal characteristics for an inverse waveguide based approach of material characterization - Bause, Fabian; Rautenberg, Jens; Henning, Bernd
A very promising approach for the ultrasonic identification of highly damping viscoelastic polymers has been proposed by Rautenberg. He uses transmission measurements through hollow cylindrical shaped test samples which are modeled as waveguides. The measurement effect relies on multiple mode-conversions at the waveguide's outer and inner boundaries and is evaluated based on an inverse approach. In this contribution we discuss different signal characteristics of the obtained dispersed signals with respect to their sensitivity to certain material parameters. Based on these sensitivities we propose a multiphase optimization scheme to increase the optimization's convergence.

Konzepte zur Regelung der Strahlungsleistung pulsbetriebener IR-Emitter - Hoof, Christian; Schlottmann, J{\; Wetzlar, Dietmar; Henning, Bernd (16. GMA/ITG-Fachtagung. Sensoren und Messsysteme)
In optischen Messeinrichtungen (Abstandsmessung, NIR-Materialfeuchtemessung) werden häufig in einem schmalen Wellenlängenbereich strahlende, gepulste Infrarot-Emitter eingesetzt. Leistungsstarke Strahlungspulse sind notwendig, führen aber zu einer thermisch bedingten Abnahme der emittierten Strahlungsleistung und zu einer Verschiebung der Maximumwellenlänge. Die hierdurch entstehenden Messunsicherheiten werden aufgezeigt und Konzepte zu deren Verringerung dargestellt.

Rekonstruktion der Phaseninformation aus Schlierenaufnahmen - Olfert, Sergei; Henning, Bernd
In der Ultraschallakustik besteht häufig die Notwendigkeit die räumliche und zeitliche Ausbreitung von Ultraschall zu charakterisieren. Das Schlierenverfahren ist ein schnelles und nichtinvasives Verfahren zur Visualisierung von Ultraschallfeldern in Flüssigkeiten. Bei diesem Verfahren wird eine ebene elektromagnetische Welle an einer Ultraschallwelle gebeugt. Das Beugungsmuster wird durch ein optisches System in der Fourierebene abgebildet. Um die mittlere Helligkeit in der Darstellung der Ultraschallwellen zu eliminieren, erfolgt eine Ortsfilterung in der Fourierebene. Als Ortsfilter werden in der Regel eine Messerschneide oder eine Punktblende eingesetzt. Hierbei wird ein Teil der Fourierebene ausgeblendet und der unbeeinflusste Anteil in Richtung des Bildaufnahmesensors transmittiert. Der Einsatz solcher Amplitudenfilter hat den Nachteil, dass die Phaseninformation einer Schallwelle in der Abbildung der Ultraschallwelle nicht erfasst wird. Der am Fachgebiet Elektrische Messtechnik der Universität Paderborn entwickelte Schlierenmessplatz ist durch ein variables Amplitudenfilter gekennzeichnet. In diesem Beitrag wird ein Verfahren vorgestellt, wie durch Kombination von unterschiedlichen Filtern die Phaseninformation einer Ultraschallwelle rekonstruiert werden kann. Hierzu werden die mathematischen Grundlagen zur Rekonstruktion der Phase hergeleitet und die ersten Messergebnisse vorgestellt.

Ein wellenleiterbasiertes Verfahren zur Bestimmung von Materialdaten für die realitätsnahe Simulation von Schallausbreitungsphänomenen am Beispiel stark absorbierender Kunststoffe - Rautenberg, Jens
Keywords: akustische Wellenleiter; Kunststoffe; Materialdatenbestimmung; Transmissionsmessung

Geführte akustische Wellen zur Flüssigkeitscharakterisierung - Rautenberg, Jens; Bause, Fabian; Henning, Bernd (Technisches Messen)
Das Spektrum akustischer Wellenleiter zur Flüssig-keitscharakterisierung reicht von der Seismologie und Geophysik mit Wellenleiterdimensionen von einigen km über die zerstörungsfreie Prüfung bis hin zur Prozessmesstechnik mit Sensordimensio-nen von wenigen mm. In diesem Beitrag wird ein phänomenologischer Weg zur Klassifizierung der Wellenleiter entwickelt, wobei stets die Oberflä-chenauslenkungen an der Wellenleitergrenze und die Anzahl der an der Wellenausbreitung beteiligten Moden Berücksichtigung finden. Im weiteren Verlauf werden Möglichkeiten zur Modellierung, Simulation und Messung multimodaler Wellenausbreitung im akustischen Wellenleiter gezeigt.

Messsystem zur Bestimmung akustischer Kenngrößen stark absorbierender, transversal isotroper Kunststoffe - Rautenberg, Jens; Bause, Fabian; Henning, Bernd
Es wird ein Wellenleiter basiertes Messsystem vorgestellt, mit dem anhand einer einzigen Transmissionsmessung alle Daten bestimmt werden können, die zur Simulation von Schallausbreitungsphänomenen in stark absorbierenden und schwach anisotropen Materialien erforderlich sind. Auf diese Weise ist es fortan möglich die akustischen Kenngrößen (winkel- und frequenzabhängige Schallgeschwindigkeiten und frequenzabhängige Absorption) verschieden konditionierter Materialproben (Temperatur, Feuchtigkeit, Alter) simultan zu erfassen. Genutzt wird dazu die mehrmalige Modekonversion an den Mantelflächen eines hohlzylindrischen akustischen Wellenleiters, wonach ein Empfangssignal mehrere Signalgruppen aufweist, deren absolute Laufzeit, Laufzeitdifferenzen und Amplituden in Abhängigkeit der Materialkenngrößen stark variieren. Grundlegend für die realisierte und in diesem Beitrag beschriebene inverse Bestimmung der akustischen Kenngrößen ist ein ganzheitliches Modell der Schallanregung, -ausbreitung und -detektion, welches die schnelle Berechnung der Empfangssignale erlaubt. Die gezielte Variation der Modell-Eingangsgrößen führt schließlich zu einer bestmöglichen Übereinstimmung zwischen berechneten und gemessenen Empfangssignalen, sodass die final angesetzten Modell-Eingangsgrößen eine gute Approximation der gesuchten materialspezifischen akustischen Kenngrößen darstellen. Im Rahmen dieses Beitrags werden der Messaufbau, wesentliche Teile der Modellierung sowie die grundätzliche Vorgehensweise zur Anwendung der inversen Messmethode gezeigt. Anhand gemessener, berechneter und mittels Finiter Elemente Methode simulierter Signale wird das Verfahren für einen Werkstoff, spritzgegossenes Polypropylen, demonstriert.

Validation of analytically modeled Leaky Lamb radiation using Schlieren photography - Rautenberg, Jens; Olfert, Sergei; Bause, Fabian; Henning, Bernd
If a guided Lamb wave leaks energy from a plate into a surrounding fluid, the radiated almost plane wave has a frequency dependent angle towards the boundary. This radia- tion angle can be calculated by numerical determination of the plates' phase velocities. We also measured the radiation angle in Schlieren photographs and found a mentionable discrepancy to the calculated angles in certain frequency regions. A first approach by modifying the boundary condition could not re- solve the observed discrepancies, but a reinterpretation of the Schlieren photographs as interference patterns of different Leaky Lamb waves leads to a good correspondence between measured and calculated values.

Blindzonenfreie Ultraschall-Abstandsmessung mit codierten Sendesignalen - Schröder, Andreas; Henning, Bernd
Bei der Ultraschall-basierten Abstandsmessung mit einem einzelnen Schallwandler ergibt sich durch das Prinzip bedingt eine Blindzone. Während und unmittelbar nach der Anregung durch das Sendesignal ist es im Allgemeinen nicht möglich, das Empfangssignal am Ultraschallwandler auszuwerten. Eine Verwendung von codierten Sendesignalen (z.B. zur Unterscheidung verschiedener Sensoren) verlängert diesen Blindbereich zusätzlich. Dieser Beitrag zeigt eine Möglichkeit zur Realisierung eines simultanen Sende- und Empfangsbetriebs mit einem einzelnen Schallwandler. Dadurch wird es möglich, die Blindzone auch bei sehr langen Sendesignalen zu eliminieren. Dazu wird der Ultraschallwandler über einen Vorwiderstand betrieben und dessen Spannung gemessen. Mittels eines mathematischen Modells kann das elektrische Sendesignal, welches am Ultraschallwandler anliegt, bestimmt werden. Die Subtraktion dieses Signals von der gemessenen Schallwandlerspannung liefert das elektrische Empfangssignal. Aufgrund von z.B. Temperatureinflüssen ändern sich die elektrischen Eigenschaften des Ultraschallwandlers ständig, wodurch eine Anpassung des Modells notwendig wird. Daher kann die Modellidentifikation nicht im Vorfeld mit einer Freifeldmessung erfolgen, sondern ist permanent während des Betriebes notwendig. Tritt dabei ein Empfangssignal z.B. infolge einer Reflexion auf, so wird die Bestimmung der Modellparameter gestört. Durch eine Bewertung der ermittelten Modelle kann die Robustheit einer Abstandsmessung erhöht werden

Luftultraschall-Abstandsmessung mit digitaler Signalverarbeitung zur Verkürzung des Mindestabstandes - Schröder, Andreas; Henning, Bernd
Ultraschall-Abstandssensoren besitzen meist nur einen Schallwandler und dadurch Prinzip bedingt einen Mindestabstand. Eine Möglichkeit diesen Mindestabstand zu reduzieren, besteht in der Realisierung eines simultanen Sendeund Empfangsbetriebes. In diesem Beitrag wird dies durch eine digitale Signalverarbeitung realisiert. Hierzu ist es notwendig, das Schallwandlersignal und das elektrische Sendesignal zu digitalisieren. Mit der Kenntnis des Schallwandlerverhaltens sowie des elektrischen Sendesignals wird das zu erwartende Schallwandlersignal modellbasiert berechnet und vom gemessenen Schallwandlersignal subtrahiert, um so das Empfangssignal zu bestimmen. Dabei liegen die Herausforderungen in der Ermittlung der Parameter eines repräsentativen Schallwandlermodells sowie der Gewährleistung einer robusten Echodetektion.

Computing roots for the analytic modeling of guided waves in acoustic waveguides - Walther, Andrea; Bause, Fabian; Henning, Bernd
Computer aided simulation of guided acoustic waves in single- or multilayered waveguides is an essential tool for several applications of acoustics and ultrasonics (i.e. pipe inspection, noise reduction). To simulate wave propagation in geometrically simple waveguides (plates or rods), one may employ the analytical global matrix method [1]. This requires the computation of all roots of the determinate of a certain submatrix. The evaluation of all real or even complex roots is actually the methods most concerning restriction. Previous approaches base on so called mode-tracers which use the physical phenomenon that solutions (roots) appear in a certain pattern (waveguide modes) and thus use known solutions to limit the root finding algorithms searchspace with respect to consecutive solutions. As the limitation of searchspace might be unstable in some cases, we propose to replace the mode-tracer with a suitable version of an interval Newton method based on Intlab [2]. To apply this interval based method, we extended the interval and derivative computation provided by Intlab such that corresponding information is also available for Bessel functions used in the circular model (rods) of acoustic waveguides. We present numerical results of a simple acoustic waveguide and discuss extensions required for more realistic scenarios.

2D phononic crystal sensor with normal incidence of sound - Zubtsoc, Mikhail; Lucklum, Ralf; Ke, Manzhu; Oseev, Alexandr; Grundmann, Ralf; Henning, Bernd; Hempel, Ulrike (Sensors and Actuators A: Physical)
The contribution presents the sensor application of a resonance-induced extraordinary transmission through a regular phononic crystal consisting of a metal plate with a periodic arrangement of holes in a square lattice at normal incidence of sound. The characteristic transmission peak has been found to strongly depend on sound velocity of the liquid the plate is immersed in. The respective peak maximum frequency can serve as measure for the concentration of a component in the liquid mixture, if a beneficial relation to the speed of sound of the liquid exists. Experimental verification has been performed with mixtures of water and propanol as model system. Here we especially pay attention to numerical calculations based on EFIT and COMSOL which reveal more insides to the wave propagation characteristics. Experimental investigations with Schlieren method and laser interferometry support the theoretical findings.

Eingebaute Selbstdiagnose mit zufälligen und deterministischen Mustern - Cook, Alejandro; Hellebrand, Sybille; Wunderlich, Hans-Joachim
Keywords: WORKSHOP

Label ranking with partial abstention based on thresholded probalistic models - Cheng, W.; Hüllermeier, Eyke; Waegeman, W.; Welker, V. (In Proceedings NIPS-2012, 26th Annual Conference on Neural Information Processing Systems, Lake Tahoe, Nevada, USA)

Probability estimation for mulit-class classification based on label ranking - Cheng, W.; Hüllermeier, Eyke (Proceedings ECML/PKDD-2012, European Conference on Machine Learning and Principles and Practice of Knowledge Discovery in Databases, Bristol, UK)

Consistent multilabel ranking through univariate loss minimization - Dembczynski, K.; Kotlowski, W.; Hüllermeier, Eyke (in Proceedings ICML-2012, International Conference on Machine Learning, Edinburgh, Scotland)

An analysis of chaining in multi-label classification - Dembczynski, K.; Waegeman, W.; Hüllermeier, Eyke (In Proceedings ECAI-2012, 20th European Conference on Artificial Inteligence, Montpellier, France)

An outlook for self-awareness in computing systems - Lewis, Peter; Platzner, Marco; Yao, Xin

Fuzzy rules in data mining: From fuzzy associations to gradual dependencies - Hüllermeier, Eyke (Combining Experimentation and Theory)

Nearly nowhere-zero r-flow graphs - Steffen, Eckhard (Discrete Mathematics)

A precise open-loop torque control for an interior permanent magnet synchronous motor (IPMSM) considering iron losses - Peters, Wilhelm; Wallscheid, Oliver; Böcker, Joachim (IECON 2012-38th Annual Conference on IEEE Industrial Electronics Society)

Cost-Effective Implementation of a Digitally Controlled LLC Resonant Converter for Application in Server- and Telecom-PSUs - Figge, Heiko; Fröhleke, Norbert; Böcker, Joachim; Schafmeister, Frank (Proc. IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM))

Novel Hybrid Modulation Schemes Significantly Extending the Reactive Power Control Range of All Matrix Converter Topologies With Low Computational Effort - Schafmeister, Frank; Kolar, Johann (IEEE Transactions on Power Electronics)

Matrixkonverter, Kapitel 3.8 - Kolar, Johann; Schafmeister, Frank (Lehrbuch Leistungselektronische Schaltungen)

Digital Slope Compensation for Current Mode Control - Schafmeister, Frank; Grote, Tobias

Novel dynamical modeling for series-parallel resonant converter - Cao, Z.; Nzeugang, F. H.; Tao, J.; Fröhleke, N.; Böcker, Joachim (21th IEEE International Symposium on Industrial Electronics (ISIE2012), Huangzhou, China)

Reduction of Total Harmonic Distortion (THD)for Interleaved Converters Operating in Discontinuous Conduction Mode (DCM) - Grote, T.; Bolte, S.; Fröhleke, N.; Böcker, Joachim (PCIM Europe Conference, Nürnberg, Germany, 2012)

High Fidelity Hybrid Hardware-in-the-Loop Simulator with FPGA and Processor for AC Railway Traction - Böcker, Joachim; Sun, M.; Cao, Z.; Tong, L.; Zou, H.; Ranjan, P. (PCIM Europe Conference, Nürnberg, Germany)

Full Digital Implementation of an Optimized Modulation Strategy for Series-Parallel Resonant Converter - Tao, J.; Cao, Z.; Sun, M.; Fröhleke, N.; Böcker, Joachim (PCIM Europe Conference, Nürnberg, Germany)

Boosting Dynamics of AC Machines by using FPGA-Based Controls - Buchholz, O.; Mathapati, S.; Böcker, Joachim (PCIM Europe Conference, Nürnberg, Germany)

Analytical and Offline Approach to Select Optimal Hysteresis Bands of DTC for PMSM - Mathapati, Shashidhar; Böcker, Joachim (IEEE Transactions on Industrial Electronics)
Keywords: Electrical and Electronic Engineering; Control and Systems Engineering

Photovoltaic inverter with high efficiency over a wide operation area - a practical approach - Preckwinkel, Heiko; Krishna, DVMM; Fröhleke, Norbert; Böcker, Joachim (IECON 2011 - 37th Annual Conference of the IEEE Industrial Electronics Society)

Time-domain steady-state modeling of series-parallel resonant converter under optimized modulation - Cao, Zhiyu; Tao, Junbing; Fröhleke, Norbert; Böcker, Joachim (IECON 2012 - 38th Annual Conference on IEEE Industrial Electronics Society)

Multi-objective optimization of LCC resonant converter applied in VLF HV generator - Hu, Manli; Fröhleke, Norbert; Peters, Wilhelm; Böcker, Joachim (IECON 2011 - 37th Annual Conference of the IEEE Industrial Electronics Society)

A comparative study of series-parallel resonant converter by using different modulation strategies - Cao, Zhiyu; Nzeugang, Franklin H.; Fröhleke, Norbert; Böcker, Joachim (IECON 2011 - 37th Annual Conference of the IEEE Industrial Electronics Society)

Analysis, design and control of 1MW, high power factor and high current rectifier system - Solanki, Jitendra; Fröhleke, Norbert; Böcker, Joachim; Wallmeier, Peter (2012 IEEE Energy Conversion Congress and Exposition (ECCE))